2009
DOI: 10.1021/bi901429y
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Phosphorylase b Kinase and Its αγδ Subcomplex as Regulatory Models for the Rabbit Skeletal Muscle Holoenzyme

Abstract: Understanding the regulatory interactions among the 16 subunits of the (αβγδ)4 phosphorylase b kinase (PhK) complex can only be achieved through reconstructing the holoenzyme or its subcomplexes from the individual subunits. In this study, recombinant baculovirus carrying a vector containing a multigene cassette was created to coexpress in insect cells α, β, γ, and δ subunits corresponding to rabbit skeletal muscle PhK. The hexadecameric recombinant PhK (rPhK) and its corresponding αγδ trimeric subcomplex were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“… a Stable αγδ subcomplexes have been isolated after expression in insect cells (58) and after dissociation of the (αβγδ) 4 complex with LiBr (48). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a Stable αγδ subcomplexes have been isolated after expression in insect cells (58) and after dissociation of the (αβγδ) 4 complex with LiBr (48). …”
Section: Resultsmentioning
confidence: 99%
“…For instance, binding of Ca 2+ to δ causes a mass redistribution on the (αβγδ) 2 lobe tips (4) where the carboxy-terminal region of α has been localized (9), and it also alters proteolysis of α near its carboxy-terminus (32). Moreover, the catalytic activities of (αβγδ) 4 and αγδ are stimulated in parallel by Ca 2+ (49, 58). There is strong indirect evidence that the effects on α of the binding of Ca 2+ to δ are mediated by γ, specifically by the γCRD, and adjacent regions of its primary structure have been shown to interact with α and δ within PhK.…”
Section: Discussionmentioning
confidence: 99%
“…Many GPCRs are over-expressed in various cancer types and they are constitutively active in malignant cells causing an aberrant response to various signals [63] . The protein Phosphorylase b kinase regulatory subunit α is a key regulatory enzyme of glycogen metabolism [64] . Glycogen can be broken down rapidly when glucose is needed, and Phosphorylase b kinase switches on another enzyme called glycogen phosphorylase b by converting it into the more active form, glycogen phosphorylase a. Alteration of KPB1 seems to be associated with muscle phosphorylase b kinase (PHK) deficiency, a rare disorder caused by mutations in the gene coding for this protein [65] .…”
Section: Discussionmentioning
confidence: 99%
“…Within the (␣␤␥␦) 4 PhK complex, the structure of ␤ is undoubtedly influenced by subunit interactions with itself and with the other three subunits, as evidenced by chemical cross-linking (7,29,30,38,54), EM three-dimensional reconstructions (10), and partial proteolysis (26). As opposed to the ␣, ␥, and ␦ subunits, which have been isolated successfully either individually (8,55,56) or in subcomplexes of PhK (57,58), the ␤ subunit appears to be stable or isolable only in the context of the intact (␣␤␥␦) 4 complex. Although the ␤ subunit undoubtedly influences the structure of ␣, ␥, and ␦ in the PhK complex, we have shown that features of an established Ca 2ϩ -dependent communication network among the ␣, ␥, and ␦ subunits are the same in both the (␣␤␥␦) 4 and ␣␥␦ complexes (57), suggesting a similar structural architecture for these subunits in each complex.…”
Section: Determination Of 2°structure Of the ␤ Subunit Within The Phkmentioning
confidence: 91%